Towards Social and Economic Prosperity: Political Legitimacy in Northern Indigenous Governance ... - Irlbacher-Fox, Stephanie (University of Alberta Library, 2012)
SSHRC Awarded IDG 2012: This project will focus on the community of Deline, Northwest Territories, a community of 600 Dene people situated on the Southwestern shore of Great Bear Lake. A group of Deline Elders wish to publish an academic book that describes their philosophy of Dene governance and have asked me to work with them to achieve this goal. An orienting oral tradition of Deline Got'ine (the people of the place where the waters flow) is the Waterheart story, or Tudzi. It describes the journey of a man to the heart of Great Bear Lake. The journey centres around the teachings of the lake's heart, teachings recognized by the people the people as foundational laws of governance. Over several years, the Elders worked with various government departments to apply this philosophy of governance to the Great Bear Lake Watershed Management Plan (GBLWMP), part of the land management approach undertaken in the context of the Sahtu Comprehensive Land Claim. However, owing to its comprehensiveness, the GBLWMP has ...